2023
DOI: 10.1021/acs.chemmater.3c02008
|View full text |Cite
|
Sign up to set email alerts
|

Mg4InSbO8 Spinel: Double 2:1 Ordering in Tetrahedral and Octahedral Sublattices and Perspective Application as an Optical Thermometer via Mn2+/4+ Doping

Zien Cheng,
Jinmei Huang,
GuangXiang Lu
et al.

Abstract: AB2O4-type spinel oxides were extensively investigated as prospective magnetic, photocatalytic, cathode, and host materials. Herein, a new Mg4InSbO8 spinel was rationally designed and structurally characterized by high-resolution X-ray powder diffraction (XRPD) in combination with neutron powder diffraction. Mg4InSbO8 crystallizes in the Imma-superstructure with lattice dimensions of a = √2/2·a C, b = 3√2/2·a C, and c = a C, where a C is the lattice parameter of the cubic (Fd3̅m) archetype spinel. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
2
3
0
Order By: Relevance
“…The highest S r value of 1.22% K −1 is obtained for MGSO:0.02Mn at room temperature (303 K) when excited at a wavelength of 280 nm. Such a high S r value is comparable to other Mn 2+ /Mn 4+ -based spinel-type optical thermometers such as 0.1 wt%Li-MgGa 2 O 4 :Mn 2+ /Mn 4+ ( S r = 1.10% K −1 ) 50 and Mg 4 InSbO 8 :Mn 2+ /Mn 4+ ( S r = 2.10% K −1 ), 45 and superior to other optical thermometric materials, such as Li 2 ZnSiO 4 :Mn 2+ ( S r = 0.682% K −1 ), 65 Sr 1.95+ x Li 1− x Si 1− x Al x O 4 F:Eu 2+/3+ ( S r = 0.83 K −1 ), 66 BaMgP 2 O 7 :Eu 2+/3+ (0.66% K −1 ), 67 La 2 LiSbO 6 :Eu 3+ /Mn 4+ ( S r = 0.89% K −1 ), 68 and Ca 2 Y 8 (SiO 4 ) 6 O 2 :Bi 3+ /Eu 3+ ( S r = 0.958% K −1 ). 69 According to the evolution trend of the S r – T curve for MGSO:0.02Mn, a much higher S r value could be expected below room temperature, manifesting its perspective application in remote and noninvasive temperature sensing at low temperatures.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The highest S r value of 1.22% K −1 is obtained for MGSO:0.02Mn at room temperature (303 K) when excited at a wavelength of 280 nm. Such a high S r value is comparable to other Mn 2+ /Mn 4+ -based spinel-type optical thermometers such as 0.1 wt%Li-MgGa 2 O 4 :Mn 2+ /Mn 4+ ( S r = 1.10% K −1 ) 50 and Mg 4 InSbO 8 :Mn 2+ /Mn 4+ ( S r = 2.10% K −1 ), 45 and superior to other optical thermometric materials, such as Li 2 ZnSiO 4 :Mn 2+ ( S r = 0.682% K −1 ), 65 Sr 1.95+ x Li 1− x Si 1− x Al x O 4 F:Eu 2+/3+ ( S r = 0.83 K −1 ), 66 BaMgP 2 O 7 :Eu 2+/3+ (0.66% K −1 ), 67 La 2 LiSbO 6 :Eu 3+ /Mn 4+ ( S r = 0.89% K −1 ), 68 and Ca 2 Y 8 (SiO 4 ) 6 O 2 :Bi 3+ /Eu 3+ ( S r = 0.958% K −1 ). 69 According to the evolution trend of the S r – T curve for MGSO:0.02Mn, a much higher S r value could be expected below room temperature, manifesting its perspective application in remote and noninvasive temperature sensing at low temperatures.…”
Section: Resultssupporting
confidence: 66%
“…74). 45 Le-Bail fitting to the XRPD patterns demonstrated that the systematic extinction conditions of our newly designed spinels are also consistent with this Imma -symmetry. Hence, Mg 4 InSbO 8 was used as an initial model in Rietveld refinements for MGSO, MGA 0.5 SO, and MASO.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The Mn 4+ ion, in octahedral coordination, has been shown to exhibit deep red to NIR emission. The Mn 2+ ion, on the other hand, exhibits green and orange-red emissions that depend on the coordination. The tetrahedral Mn 2+ ions exhibit a green emission, while octahedral Mn 2+ ions exhibit an orange-red emission. Recently, the use of Mn 2+ and Mn 4+ ions in a spinel lattice has been shown to exhibit a tunable emission …”
Section: Introductionmentioning
confidence: 99%
“…32−38 Recently, the use of Mn 2+ and Mn 4+ ions in a spinel lattice has been shown to exhibit a tunable emission. 39 We have been investigating mineral structures to generate new colored compounds 40−43 and for white-light emission. 44 In continuation of this theme, we have now taken up the study of compounds based on the tululite mineral, Ca 14 Zn 6 A 10 O 35+x (A = Al and Ga; 0 ≤ x ≤ 1).…”
Section: ■ Introductionmentioning
confidence: 99%